Operative and Espoused Personnel Selection Criteria of Managers - Singh, Jang; Crocker, Olga (Relations industrielles / Industrial Relations, 1988)
This article reports the findings of a study of operative and espoused personnel selection criteria of managers. A projective test (derived front Kelly's Rep Test and Brown's Personnel Decision Analysis Form) was used to elicit and measure the strength of operative selection criteria while a short questionnaire sought demographic data and espoused selection criteria.